«NEW ECONOMY» AND ITS RESOURCE POTENTIAL - N. L. Gribanova (Наука и техника)
The paper considers a number of methodological approaches to a definition of the «new economy» concept and its resource potential, points out significant features of new-type economy and defines a criterion of the «new economy» correlation with informational and global economy. The role and importance of the human capital, science and education in the development of «new economy» are studied in the paper. The paper emphasizes the importance of the participation of the Republic of Belarus in «new economy» for more efficient realization of the main competitive advantages of our country.